A Silvi-pastoral System to Optimise Resource Use for Biomass Production from the Bouldery Riverbed Lands of Doon Valley - Lal, H.; Singh, Charan; Puri, D. N.; Vishwanatham, M. K. (Indian Forester, 2000)
A field experiment was conducted for nine years (1986-1995) to study the effect of plant spacing of Eucalyptus hybrid grown in association with Chrysopogon fulvus on plant growth, fresh and dry matter production and nutrients uptake of both tree and grass on degraded bouldery riverbed land of Do on Valley. It is evident from study that Eucalyptus hybrid planted at 3m x 1.5m spacing with Chrysopogon fulvus was found optimum with regard to plant growth, survival, dry matter production and nutrients uptake as compared to 3mx1m and 3mx3m spacings. Similarly, Chrysopogon fulvus grown alone exhibited better plant growth, produced relatively more fresh and dry fodder and improved the nutrients content and their uptake considerably than those grown with Eucalyptus hybrid planted at 3m x 1.5m and 3m x 1m spacings.